PENERAPAN AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KELURAHAN NUSA INDAH KOTA BENGKULU - Derrian dwi Anggara; Ummul Khair (Universitas Muhammadiyah Bengkulu, 2024)
The existence of accounting in MSMEs activities can help and make it easier for business actors to know profits and decide what steps to take. This study aims to determine the application of accounting to micro, small and medium enterprises in Nusa Indah Village, Bengkulu City. This research is a type of descriptive qualitative research with data collection carried out through questionnaires and interviews. The object of this research is MSMEs Actors located in Nusa Indah Village, Bengkulu City, as many as 13 MSMEs Actors. The results showed that there are still many MSMEs actors who do not understand accounting in depth, and the financial statements that have been presented are still very simple (not in accordance with SAK EMKM). Other obstacles faced by business actors are the lack of socialization or training on accounting in accordance with SAK EMKM, the assumption that financial statements are difficult to understand, and the low awareness of business actors to improve the presentation of financial statements in accordance with SAK EMKM. Keywords:Implementation of Accounting, Micro, Small and Medium Enterprises (MSMEs), SAK EMKM